The impact of the "Think-Pair-Participate" strategy on the science processes of the first intermediate grade students (Journal of the College of Basic Education, 2023)
Our current era is characterized by being an accelerated era in all fields, especially at the cognitive level, so attention must be paid to teaching and learning strategies and the effective role they play in improving the learning environment and increasing interaction between the teacher and the learner to reach educational results that keep pace with the spirit of the times and fulfill the aspirations of educators. The problem of the current research lies in the methods The traditional methods adopted in schools currently, as some of them do not fit with the contemporary scientific development. Therefore, the problem of the current research was identified in the following question:What is the effect of the strategy of "Think-Pair-Share" on the science processes of the first intermediate grade students?The research aimed to find out the impact of the (Think-Pair-Participate) strategy on the science processes of the first intermediate grade students.In order to achieve the goal of the research, the following zero hypothesis was put forward: "There are no statistically significant differences at the level (0.05) between the mean scores of the experimental group students who studied according to the strategy (Think-Pair-Share) and the average scores of the control group students who studied according to the usual method." In testing science processes.In order to verify the validity of this hypothesis, the researcher conducted an experiment that lasted a full semester, and the researcher adopted the experimental approach with equal groups with a post-test for the science processes of the students. Distributed into two divisions, one of which represented the experimental group (33) students who studied according to the strategy (Think-Pair-Share TPS) and the other represented the control group (34) students, and the two groups were rewarded in the variable (intelligence, age, previous information, science processes).The researcher prepared the research tool represented by the science operations test, consisting of (30) objective items of the type (multiple choice), and the difficulty, discriminatory power, and the effectiveness of the wrong alternatives were calculated for each of the items of the test, and its validity was calculated, and then the stability of the test was extracted using the (Queder) equation - Richardson 20), as the stability of the science operations test was (0.815).